2008
DOI: 10.1080/08977190802194317
|View full text |Cite
|
Sign up to set email alerts
|

mRNA expression of members of the IGF system in the organ of Corti, the modiolus and the stria vascularis of newborn rats

Abstract: We analyzed the mRNA expression of the insulin-like growth factor (IGF) family genes and of selected downstream pathway genes using the Affymetrix microarray system and confirmatory RT-PCR in the freshly prepared organ of Corti (OC), modiolus (MOD) and stria vascularis (SV) from neonatal rats (3-5 days old) and after 24h in culture. Among the seven members of the IGF family analyzed in this paper, IGF1, IGF2 and IGF-binding protein (IGFBP2) had the highest basal expression in all regions. Preparatory stress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…In freshly prepared tissue, about 2-10 % of all nuclei were found to be stained by propidium iodide, indicating cell damage during preparation of the cochlear tissue. After 24h in culture, the number of necrotic cells in the MOD region increased from 8 % to 25-35 %), whereas the number of such cells remained unchanged in the OC and SV regions (Gross et al, 2008). Gene expression markers indicate that two basic pathogenetic mechanisms are involved in this experimental model: mechanically induced inflammation and hypoxia.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In freshly prepared tissue, about 2-10 % of all nuclei were found to be stained by propidium iodide, indicating cell damage during preparation of the cochlear tissue. After 24h in culture, the number of necrotic cells in the MOD region increased from 8 % to 25-35 %), whereas the number of such cells remained unchanged in the OC and SV regions (Gross et al, 2008). Gene expression markers indicate that two basic pathogenetic mechanisms are involved in this experimental model: mechanically induced inflammation and hypoxia.…”
Section: Introductionmentioning
confidence: 95%
“…Fragments of one ear were kept in culture under normoxic conditions, fragments of the second ear were exposed to moderate hypoxia (oxygen partial pressure inside the culture medium was 10-20 mm Hg) for 5 h, starting three hours after plating. The number of dead cells was determined in freshly prepared tissue (controls) and after 24 h in culture using the live/dead viability test by propidium iodide (PI) and calcein AM staining (Gross et al, 2008).…”
Section: Explant Culturesmentioning
confidence: 99%
“…B: Propidium iodide (PI)-stained nuclei. Data from Gross et al (2008) [5] ; data indicate mean and SEM (% PI-cells, n = 12 for MOD, n = 4 for SV and OC). *p<0.01, **p>0.001.…”
Section: Research Articlementioning
confidence: 99%
“…Analysis of gene expression showed that two basic pathogenetic mechanisms are involved in this experimental model: mechanically induced inflammation and hypoxia [4] . To compare the expression changes with the cell death rate, we in parallel determined the proportion of dead cells immediately after tissue preparation and after 24 h in culture [5] . After 24 h, the cell death rate increased to about 25-30 % in the MOD, but did not change significantly in the OC and SV regions (Fig.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation